Evaluation of Overall Resource Effectiveness for Job Shop Production System - Dawood, Lamyaa Mohammed; Khudairb, Anat Amer (Anbar Journal of Engineering Sciences, 2019)
ORE addresses various kinds of losses associated with manufacturing system which can be targeted for initiating improvements. Evaluating ORE will is helpful to the decision maker(s) for further analysis and continually improves the performance of the resources. Overall Resource Effectiveness (ORE) encompasses seven factors are; performance, quality rate, readiness, changeover efficiency, availability of material and availability of manpower. In this research Job shop production of General Company for hydraulic industries, with focus on Damper and Tasks Factory (DTF)is tested as a case study for two of the most customer demand rear dampers (Samaned and Nissan). Data are collected and analyzed for years 2016-2017 to evaluate of ORE values. Results show that process performance factor among other seven factors have the less value causing the highest loss in ORE decrease. Where the highest ORE value is (58.6%) for Nissan and (69.3) for Samaned rare production. Also, time loss due to set up time is detected where it ranges from 3% to about 13% per month for the above mentioned two tested dampers. Results are generated employing Minitab Version 17, Quality Companion Version 3 soft wares. It is recommended to introduce SMED (Single Minute Exchange of Dies) concept that could decrease losses in set up time .Also improvements in maintenance programs are vital, and above all improving process performance values is essential by employing lean manufacturing that result in fast outcomes ,and TQM process improvement strategy for long term outcomes these two process performance strategies may enhance ORE values therefore, decrease losses, and consequently increase quality and productivity.